Symposium 12: Information Society Studies in Practice - a Networked Learning Case Study - Pinter, Robert (Proceedings of the International Conference on Networked Learning, 2008)
NETIS (Network for Teaching Information Society) is a consortium, the aim of which is to develop a course as part of a two-year programme (2006-2008), with the support of the European Union funded Leonardo da Vinci Programme. The course prepared by NETIS is designed to provide an introduction to information society studies mainly for undergraduate students. Our aspiration is that a model course will be designed based not only on the prepared teaching materials but also on the experiences of teachers as well as students, and that it will hopefully be regarded as being of a high standard all over Europe. The course book was published first in Hungarian in 2007 and will be published in English and Greek in 2008, and prepared in printed, in Moodle and in CD versions. Obviously it is not only students who can benefit from a course book like this but also teachers, researchers, experts and all those who find this area interesting. Because the book is written in modules with each topic as an independent unit in itself as well as part of the larger whole, it is not necessary to read the course book in its entirety. The book covers the following topics: the concept, theory and history of the information society, the social role of technology, the network society and economy, the use of space and changes in social relations pertaining to space, the growing significance of innovation in the economy and in society, issues of legal regulation, the information society strategy of the European Union, electronic government and administration, the digital divide and e-equal opportunities, digital culture, the digitalisation of the cultural heritage, information literacy, electronic education, life long learning. The course book is supplemented with a separate collection of readings to provide further help to students (i.e. textbook with studies, student papers and country reports). Based on these materials courses were taught in several institutions of higher education from the autumn of 2007 in Hungary, England, Greece and Slovakia, both through traditional learning and e-learning. Based on the results from teaching and research findings of our project we can describe the experiences of students and teachers, their expectations and impressions. The aims of this research are to give methodological advice to teachers on how to teach our course book, to teach information society in general, to teach a blended learning course with the use of a Moodle system, and to teach in a network with other teachers and students. NETIS also helps to understand the adoption of such materials and curriculum in different countries. The conclusions are beneficial not only for teachers and researchers on information society but also for any teacher who plans to use e-learning systems, plans to teach a blended learning course, plans to have networked learning or organizes international collaboration in education. The NETIS team introduces the project itself, and its general experience in a separate panel at the 6th Networked Learning Conference: teaching methods regarding networked learning based on feedback from students and teachers and cultural aspects of the project. This article provides the general introduction for the project and the other papers concentrate on the results in the most important fields.